Self-healing at the nanoscale : mechanisms and key concepts of natural and artificial systems - Amendola, Vincenzo; Meneghetti, Moreno (Boca Raton : CRC Press, 2012)
'Self-healing materials have the ability to repair damage caused by mechanical use over time, similar to how biological systems heal themselves after being wounded. This book presents the general strategy and key concepts of self-healing systems, repairing mechanisms at the nanoscale, and the role of nanostructures in these systems. The text covers natural systems, including both spontaneous healing mechanisms and biological repair mechanisms, as well as artificial systems, including nanostructured and macroscopic systems. It also reviews a series of systems that show potential for building self-healing devices or for inspiring self-healing devices. Discusses natural self-healing processes. Introduces natural and artificial self-healing systems. Presents both experimental and computational methods. Focuses on the mechanisms at the atomic, molecular, and nanometric level'--
Includes bibliographical references and index.
Keywords: Self-healing materials; Nanostructured materials; SCIENCE / Chemistry / General; TECHNOLOGY & ENGINEERING / Material Science